La2SrSc2O7: A‑Site Cation Disorder Induces Ferroelectricity in Ruddlesden–Popper Layered Perovskite Oxide - Yi, Wei; Kawasaki, Tatsushi; Zhang, Yang; Akamatsu, Hirofumi; Ota, Ryo; Torii, Shuki; Fujita, Koji (Journal of the American Chemical Society, 2024)
Rational design of ferroelectrics in layered perovskites, like n = 2 Ruddlesden–Popper (RP) phase A 3 B 2O7, has been achieved by the hybrid-improper ferroelectric (HIF) mechanism, in which an electric polarization is induced via a trilinear coupling to nonpolar BO6 octahedral rotation and tilt distortions around crystallographic axes. In the present work, hybrid improper ferroelectricity in n = 2 RP-type La2SrSc2O7 induced by the disordering of Sr2+/La3+ cations on the A-sites in rocksalt ([Sr/La]Rs = 25/75) and perovskite ([Sr/La]Pv = 50/50) layers is demonstrated through experimental and theoretical investigations. The ferroelectric A21 am structure (a – a – c + in Glazer notation) at room temperature and the second-order phase transition to paraelectric Amam structure (a – a – c 0) at T C ∼ 600 K are determined by a combination of X-ray and neutron diffraction and optical second harmonic generation. The ferroelectric hysteresis loop measurements prove the switchable electric polarization indicative of ferroelectricity. These results represent an unprecedented example of ferroelectricity in the n = 2 RP family of Ln2AB2O7 with inequivalent Ln 3+ and A 2+ cations. Combining the abovementioned experimental results with the first-principles calculations, we verify the role of Sr/La distributions in regulating the interlayer rumpling, which, in addition to the structural tolerance factor, is key to controlling the structural distortions of RP phases. The stabilization of the ferroelectric, a – a – c + distorted structure is a consequence of the disordered Sr/La distribution on the A-sites, which suppresses the rumpling-induced octahedral deformations in competition with the octahedral rotations and thus enables the concurrence of a 0 a 0 c + rotations and a – a – c 0 tilts required for the HIF mechanism. This work demonstrates the possibility of altering the crystal symmetry of RP phases through the A-site cation disorder and provides a complementary approach to the rational design of new HIF materials.